A 3D Lagrangian meshfree projection-based solver for hydroelastic Fluid–Structure​ Interactions. (August 2021) - Khayyer, Abbas; Gotoh, Hitoshi; Shimizu, Yuma; Nishijima, Yusuke
Abstract: The paper presents a 3D entirely Lagrangian meshfree solver for reproduction of fluid–structure interactions (FSI) corresponding to incompressible fluid flows and elastic structures. A projection-based particle method, namely, Moving Particle Semi-implicit (MPS), is coupled with a Hamiltonian particle-based structure model, referred to as Hamiltonian MPS (HMPS) structure model. The HMPS structure model is configured in the framework of Hamiltonian mechanics through consideration of the Lagrangian for a system of particles from which the motion equation for non-linear elastodynamics is derived via variational principles. The stability, accuracy and energy/momentum conservation properties of HMPS structure model are verified by four benchmark tests. The MPS and HMPS models are then coupled through application of a mathematically–physically compatible coupling scheme. The accuracy, stability, convergence and conservation properties of the presented 3D MPS–HMPS hydroelastic FSI solver are verified by considering four FSI benchmark tests. To the best of our knowledge, the paper presents the first 3D entirely Lagrangian meshfree hydroelastic FSI solver in the context of projection-based particle methods. In addition, through incorporation of a multi-resolution scheme the adaptivity of the proposed solver is also portrayed. Highlights: The first 3D entirely Lagrangian meshfree projection-based hydroelastic FSI solver is presented. The structure model is based on Hamiltonian mechanics with the equation for non-linear elastodynamics. Comparative study is conducted with respect to an extended classical MPS structure model. The structure model and FSI solver are verified through a total number of eight benchmark tests. The structure model and FSI solver are shown to possess notable stability, accuracy and conservation properties.